Baby Jake's birthday - Sandelin, Karen; Letheby, Lavinia (Kersbrook, South Australia : Clever Speller Pty Ltd, 2018)
"Jamie and Jane are in charge of the games for Baby Jake's first birthday party... Read about the fun at the party...and easily learn 9 ways to spell the long A sound. This engaging phonics story brings spelling to life and contains 103 Long A words, providing authentic context to make sense of phonics. Clever Speller's unique story based learning style makes learning to spell a happy time. Suitable for students aged 4-10 to: Develop phonemic awareness; Learn all the ways to spell sounds in words; Polish with grammar. Learn to spell naturally with stories" -- Cover description.
"Learn to spell with stories" -- at head of cover.
Keywords: Reading -- Phonetic method; English language -- Orthography and spelling; Electronic books